Innovative and industrially viable approach to fabricate AlOx rear passivated ultra-thin Cu(In, Ga)Se2 (CIGS) solar cells. (1st September 2020) - Birant, Gizem; de Wild, J.; Kohl, T.; Buldu, D.G.; Brammertz, G.; Meuris, M.; Poortmans, J.; Vermang, B.
Highlights: Novel and industrially relevant rear surface passivation approach for CIGS ultra-thin solar cells. Atomic-layer-deposited Al2 O3 is used as a passivation layer. Spin-coated alkali solution is used to create point contacts. Top-view SEM image of point contacts and supportive EDS analysis is presented. A significant increase in open-circuit voltage is achieved. Abstract: In this work, an industrially viable and novel rear surface passivation approach for Copper Indium Gallium di-Selenide, Cu(In, Ga)Se2, CIGS, ultra-thin (500 nm) solar cells is developed. The passivation layer was deposited by atomic layer deposition (ALD), and an alkali treatment was applied via spin coating. It was observed that selenization of the samples is required to create contact openings. The openings were visualized by SEM, and these results were supported by EDS. The impact of the oxide layer's thickness, as well as the alkali solution's molarity, was studied. Solar cells were produced for the optimal combination of these two parameters. As a result, with a relative 13% increase, the highest Voc of 623 mV was achieved. Hence, the efficiency of the passivated solar cell was relatively increased by one-third, by using an industrially feasible, fast, and repeatable technique.